Solar district heating in the People Republic of China status and development potential. (ADB briefs., 2019)
It explores the significant potential of solar district heating to accelerate the integration of renewable energy into heating systems in the PRC. This will be important in promoting low carbon cities and reducing urban air pollution. The study highlights that solar district heating (SDH) can provide high efficiency and reliability as well as environmental benefits. It finds that SDH has considerable market potential in the PRC and proposes practical ways forward. The study will also be of interest to other Asian countries that face similar challenges.